Pengaruh Kepercayaan Dan Kualitas Pelayanan Terhadap Keputusan Pengguna Jasa Transportasi Bus Damri Palembang - Tanjung Enim - Sari, Mariskha Nopita; Valianti, Reva Maria; Heryati, Heryati (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to test the hypothesis of the influence of trust and service quality on the decisions of DAMRI Palembang - Tanjung Enim Bus Transportation Service users. The sampling technique was nonprobability sampling or saturated sampling, the number of samples in this study were 40 respondents. Using instrument test, validity test, reliability test. The classic assumption test is the normality test, multicollinearity test and heteroscedasticity test. The data analysis technique used in this study is multiple linear analysis, correlation analysis, determination analysis, t test and F test.The results of the hypothesis test concluded that partially there is an effect of trust (X1) on service user decisions with a significant value of 0.000 <0.05, meaning that partially there is a significant influence on user decisions. The simultaneous F test results obtained a significant value of 0.000 <0.05, which means that Ha is accepted and HO is rejected. So, it can be concluded that there is a significant influence simultaneously on trust and service quality on the decisions of users of DAMRI Palembang - Tanjung Enim Bus Transportation Services. The test results are strengthened by a correlation test of 0.834 and a determination test of 696 which shows the results of the discussion and then have a very strong relationship so that they can form an explanation of 69.6%, the rest is influenced by other factors. Keywords: Trust, Service Quality, User Decision